Polish women employed in the United Kingdom and their understanding of professional success - Florian, Ewa (Adult Education Discourses, 2020)
The aim of the article is to show how self-employed Polish women living in the UK perceive professional success. The main assumption adopted in this article is based on the stereotypical model of a male entrepreneur and the social division of labour, which is being renegotiated by immigrant women are beginning to shape their own model a professionally active, successful woman. The theoretical framework of the analysis is determined by the definitions of the objective and subjective dimensions of success and the relationships between them, as well as the concepts and results of research on women in the labour market and their approach to a professional career. The empirical part of the work is based on the results of qualitative research (27 individual, in-depth interviews) conducted among self-employed Polish women in the United Kingdom. An intersectional perspective was used in the data analysis. Based on the research, it has been established that the subjective dimension of the professional success of self-employed immigrant women includes, among others, definitions such as material success, success as job satisfaction and success as a balance between work and family life.